Analisis Pengaruh Penggunaan Media Sosial Instagram Terhadap Customer Engagement dan Customer Loyalty (Studi Pada Followers Akun Instagram Shopee Food) - Fathonah, Mutiara; Ruskan, Endang Lestari (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The COVID-19 pandemic that hit the world has made many changes in various fields, one of which is technology. This makes the emergence of new technologies that support people's lives. One of them is an online food delivery service application that can help people's lives during a pandemic. Seeing this, one of the Shopee applications has created its Shopee Food feature. To promote and assist users in using Shopee Food, Shopee Food is increasing its CRM activities, especially SCRM (Social Customer Relationship Management), namely implementing CRM activities through social media using the Instagram account @shopeefood_id. Therefore, this research is focused on seeing whether SCRM activities via Instagram @shopeefood_id can affect customer relationships, especially customer engagement and customer loyalty. This study used a quantitative-based survey research method with a sample of 100 respondents. The results of this study state that Social Customer Relationship Management has a positive and significant effect on Customer Engagement, Social Customer Relationship Management has a positive and significant effect on Customer Loyalty, Customer Engagement has a positive and significant effect on Customer Loyalty, and Social Customer Relationship Management has an indirect effect directly to Customer Loyalty through Customer Engagement.